Corruption as Seen in Mark Twain’s Short Story The Man Who Corrupted Hadleyburg - Gerung, Grace; Wuntu, Ceisy N.; Rorimpandey, Rinny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This study aims at analysing the story's portrayal of corruption. This study is a qualitative research, and this study employed an objective approach of M.H Abrams in analysing the data of corruption as seen in "The Man Who Corrupted Hadleyburg". As the results, there are four types of corruption such as, Moral corruption is exemplified through the characters' susceptibility to greed and the erosion of their moral values when faced with the temptation of wealth. Ethics corruption is evident in the hypocrisy of Hadleyburg's residents, who, despite their outwardly virtuous appearances, succumb to deceitful practices when their integrity is challenged. Justice corruption is depicted in the manipulation of the town's justice system, emphasizing the ease with which corruption can infiltrate seemingly infallible institutions. Social corruption is explored through the ripple effect of dishonesty, showcasing how a single act of corruption can contaminate the entire social fabric of a community. In light of these findings, a fruitful avenue for further research on the themes of moral corruption, ethics corruption, justice corruption, and social corruption in "The Man Who Corrupted Hadleyburg" could involve a comparative analysis with contemporary societal dynamics. Investigating how the depicted corrosive influences manifest in modern settings, exploring real-world instances of moral and ethical lapses, compromised justice systems, and social decay would provide insights into the enduring relevance of Mark Twain's narrative